Guvernare şi bugete publice europene în perioada de criză - Stanciu, Mariana (Calitatea Vieții, 2012)
The article shows the increasing common trends regarding governing of the EU member states, and some important evolutions în financing the public field in EU countries, during the crise started in 2008. In the context are also described many excepting situations regarding the Romanian budgetary policies.